ERROR ANALYSIS IN CLAUSE USAGE OF BAHASA INDONESIA IN CHAPTER ONE OF THE THESIS BY A PBSI STUDENT AT UNMUS “ANALISIS KARAKTER TOKOH UTAMA DALAM FILM A STREET CAT NAMED BOB BY ROGERS SPOTTISWOODE” BY YOLENTA OKTOVIA MAHUZE - Ekfindar Diliana (Acceleration: Multidisciplinary Research Journal, 2024)
The focus of this study is the errors in the clause usage in chapter one in student’s thesis majoring  Indonesian Language and Literature Education at Musamus University--"Character Analysis of the Main Character in the Film A Street Cat Named Bob by Rogers Spottiswoode" by Yolenta Oktovia Mahuze. This study aims to (1) analyze language errors in the field of clauses in the object of study (2) find out the factors that cause these errors (3) find out effective ways to reduce language errors. The author decided to choose descriptive qualitative method in conducting the research. The result of this analysis was there were some clause errors such as the addition of auxiliary verbs in equational clauses, ineffective sentences, and the omission of verbs in intransitive clauses. There were several factors that influence a person to make language mistakes; they were, the influence of the mother tongue (B1) which was too strong, the influence of the environment and habits, the use of inappropriate foreign terms, and the use of spelling that is not in accordance with the KBBI. However, to minimize this, expand language skills and build habitual language skills.